SISTEM INFORMASI KLINIK BERBASIS WEB PADA KLINIK UMUM DAN KECANTIKAN DOKTER GALUH DWI ANANDHITA JAKARTA - Monalisa Monalisa; Irfan Mahendra (CKI ON SPOT, 2017)
Doctor Galuh Dwi Anandita Health and Beauty Clinic is a public health and beauty-care facilities in South Jakarta. Currently, the administrative and operational management of Doctor Galuh Dwi Anandita Health and Beauty Clinic, is still done manually. This condition causes the quality of services rendered to be low, because the information needed for decision-making processes are often late and inaccurate, which could also impact on delays or errors in the process of making medical treatment given to the patient. Implementation of Web-based clinical information systems in Doctor Galuh Dwi Anandita Health and Beauty Clinic is seen to be the solution to these problems.